Ultrafast fiber lasers with low-dimensional saturable absorbers: Status and prospects - Debnath, Pulak Chandra; Yeom, Dong Il (Sensors, 2021)
Wide-spectral saturable absorption (SA) in low-dimensional (LD) nanomaterials such as zero-, one-, and two-dimensional materials has been proven experimentally with outstanding re-sults, including low saturation intensity, deep modulation depth, and fast carrier recovery time. LD nanomaterials can therefore be used as SAs for mode-locking or Q-switching to generate ultrafast fiber laser pulses with a high repetition rate and short duration in the visible, near-infrared, and mid-infrared wavelength regions. Here, we review the recent development of emerging LD nano-materials as SAs for ultrafast mode-locked fiber laser applications in different dispersion regimes such as anomalous and normal dispersion regimes of the laser cavity operating in the near-infrared region, especially at ~1550 nm. The preparation methods, nonlinear optical properties of LD SAs, and various integration schemes for incorporating LD SAs into fiber laser systems are introduced. In addition to these, externally (electrically or optically) controlled pulsed fiber laser behavior and other characteristics of various LD SAs are summarized. Finally, the perspectives and challenges facing LD SA-based mode-locked ultrafast fiber lasers are highlighted.
Keywords: Carrier recovery time; Mid-infrared wavelengths; Near infrared region; Non-linear optical properties; Saturable absorption; Saturation intensity; Two-dimensional materials; Ultrafast fiber lasers; Low-dimensional materials; Optically/electrically controlled fiber lasers; Saturable absorber; Ultrafast fiber laser